Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1128/am.18.5.834-837.1969
|View full text |Cite
|
Sign up to set email alerts
|

Congo Red-Agar Plating Medium for Detecting Pigmentation in Pasteurella pestis

Abstract: Ability to detect pigmented and nonpigmented Pasteurella pestis is essential in plague research, and is currently dependent on use of the synthetic hemin-agar of Jackson and Burrows. We have devised a new differential medium for this purpose, containing Congo red dye and common, commercially available laboratory media. The ease and simplicity of preparation make the Congo red-agar a practical routine laboratory tool in plague research. These findings, possibly indicating a common bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…During routine lab culture, Y. pestis incurs spontaneous loss of a 102-kb locus, referred to as the pigmentation locus ( 56 ), or Pgm locus, named for the ability to form pigmented colonies on CR-supplemented agar ( 57 ). The hmsHFRS operon is located within the pgm locus and confers this phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During routine lab culture, Y. pestis incurs spontaneous loss of a 102-kb locus, referred to as the pigmentation locus ( 56 ), or Pgm locus, named for the ability to form pigmented colonies on CR-supplemented agar ( 57 ). The hmsHFRS operon is located within the pgm locus and confers this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains and plasmids used in this study are listed in Table S1 in the supplemental material. The Y. pestis KIM6+ (pCD1 − ) strains were cultured on Congo red-heart infusion agar ( 57 ) to confirm the presence of the hmsHFRS locus prior to subsequent culturing. Strains were grown at 25°C with shaking unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the ability to bind to hemin in certain pathogenic bacteria is strongly associated with their ability to bind Congo red [14][15][16]. In a study of oral spirochetes (Treponema denticola, Treponema vincentii, and Treponema socranskii), the hemin binding property of bacteria was reported to be associated with Congo red binding [15].…”
Section: Introductionmentioning
confidence: 99%
“…38103. common sugar in indicator cells of other species. However, sensitive cells of Y. pestis, in addition to being Pst-, are also able to absorb certain exogenous pigments (pgm+) such as hemin (14) or Congo red (28). The mutation to pgm-in Pst-cells of Y. pestis results in resistance to pesticin (5).…”
mentioning
confidence: 99%